Democracy in Kyrgyzstan: problems and specific features - Urmanbetova, Zhyldyz (Opción, 2019)
The article examines the state of democracy in the Kyrgyz Republic, with an emphasis on understanding democracy through the lens of the political consciousness, social memory and spiritual and cultural values of the Central Asian republic via comparative and typological methods. The result of the article shows the struggle between the new political culture and the traditional political order, which channels the democracy development in a specific direction. In conclusion, it may be reasonable to study further the existence of the hybrid regime as it applies to the situation in Kyrgyzstan before the transition to a parliamentary government.